The One Health stewardship of colistin as an antibiotic of last resort for human health in South Africa. Issue 9 (September 2018) - Mendelson, Marc; Brink, Adrian; Gouws, Joey; Mbelle, Nontombi; Naidoo, Vinny; Pople, Troy; Schellack, Natalie; van Vuuren, Moritz; Rees, Helen
Summary: Increasing reliance on antibiotics of last resort to treat the rising numbers of multidrug-resistant bacterial infections in people has focused attention on how shared-use antibiotics are managed and regulated across human and animal health. Discussions at international and national levels have intensified since the identification of new plasmid-mediated genes for colistin resistance in 2016, first in China and subsequently in many other countries, removing the last line of defense against multidrug-resistant Gram-negative bacterial infections with carbapenem resistance. South Africa has reacted to this threat by doing a situational analysis and review of the existing legislation concerning colistin use in animals and people, to inform which course of action to take. The experiences shared in this Personal View outline the process, institution of governance with widespread stakeholder engagement, surveillance, and interventions that South Africa has taken towards optimising the shared use of colistin. The instigation of stewardship guided by the principles of the One Health concept for shared-use antibiotics at the country level is a crucial component of any action plan to combat antibiotic resistance, and is as relevant to other existing antibiotics and new chemical entities that will be forthcoming from an invigorated antibiotic pipeline as it is to colistin.